Case Report: Successful management of hepatic injury secondary to mercury (II) oxide poisoning in a Vulpes lagopus with tail gland infection - Yang, BaoLian; Qiu, ZongSheng; Wei, ChengWei; Ma, TianWen (Frontiers in Veterinary Science, 2026)
A 6.08 kg female stray Arctic fox (Vulpes lagopus) of unknown age was presented with tail gland inflammation. Initial conventional therapy and subsequent tail amputation at a primary veterinary facility resulted in limited improvement. Subsequently, a topical medication red mercuric oxide (Hydrargyri Oxydum Rubrum) was applied for 4 weeks. Although the local infection showed signs of improvement, the fox subsequently developed progressive systemic signs, including anorexia, dark urine, and weight loss, prompting referral. Clinical examination revealed a large amount of cherry-red medication covering the wound. Hematological tests indicated elevated neutrophils and C-reactive protein (CRP), suggesting an inflammatory response. Serum biochemistry revealed elevated levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), and total bile acids (TBA), indicating hepatobiliary injury, alongside an elevated creatine kinase (CK) suggestive of abnormal muscle metabolism. The whole-blood mercury concentration was significantly elevated (4.7583 μg/L). Imaging findings included: ultrasound showing gallbladder sludge, abnormal liver parenchyma echogenicity, and indistinct kidney contours; X-ray revealed gastric gas, liver edge extending beyond the costal arch, blurred renal contours, and significantly increased density in the tail gland area. The Arctic fox was diagnosed with chronic topical mercury (II) oxide-induced mercury poisoning and secondary liver injury. The treatment regimen included: (1) removal of the topical medication and surgical debridement; (2) intravenous administration of reduced glutathione (hepatoprotection), ceftiofur sodium (anti-infective), and vitamin C (antioxidant); (3) oral administration of a mercury chelating agent (dimercaptosuccinic acid) and choleretics (ursodeoxycholic acid); and (4) intramuscular injection of appetite stimulants. After 4 weeks of systemic treatment, the fox’s abnormal biochemical parameters returned to normal, and the prognosis was good. This case addresses a specific gap in the diagnosis and treatment of heavy metal poisoning in wildlife. It provides a valuable reference for the clinical management of poisoning cases associated with topical mercury-containing wound medications.